2022
DOI: 10.1136/thoraxjnl-2021-218275
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal lung abnormalities following hospitalisation for COVID-19 and viral pneumonitis: a systematic review and meta-analysis

Abstract: IntroductionPersisting respiratory symptoms in COVID-19 survivors may be related to development of pulmonary fibrosis. We assessed the proportion of chest CT scans and pulmonary function tests consistent with parenchymal lung disease in the follow-up of people hospitalised with COVID-19 and viral pneumonitis.MethodsSystematic review and random effects meta-analysis of proportions using studies of adults hospitalised with SARS-CoV-2, SARS-CoV, MERS-CoV or influenza pneumonia and followed up within 12 months. Se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
75
3
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 117 publications
9
75
3
7
Order By: Relevance
“…Although functional recovery from severe COVID-19 pneumonia occurs within 1 year after discharge, approximately one third of patients (39.8%) still have decreased DLCO. These findings are in line with the results from a Chinese cohort [ 15 ], albeit excluding patients requiring invasive mechanical ventilation, and are consistent with a recently published meta-analysis [ 34 ]. Among our key findings is that although more severe patients showed higher diffusion impairment 2 months after discharge, this difference lost significance at 6 and 12 months.…”
Section: Discussionsupporting
confidence: 92%
“…Although functional recovery from severe COVID-19 pneumonia occurs within 1 year after discharge, approximately one third of patients (39.8%) still have decreased DLCO. These findings are in line with the results from a Chinese cohort [ 15 ], albeit excluding patients requiring invasive mechanical ventilation, and are consistent with a recently published meta-analysis [ 34 ]. Among our key findings is that although more severe patients showed higher diffusion impairment 2 months after discharge, this difference lost significance at 6 and 12 months.…”
Section: Discussionsupporting
confidence: 92%
“…Data from a recently published review show that approximately 20% of COVID-19 patients progress to fibrotic sequelae that persist until the one-year follow-up [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although most patients improve over time, a systematic review and meta-analysis of studies within one year following hospitalization demonstrated the presence of opacities suggestive of lung fibrotic lesions in almost one third of the exams (0.29; 95% CI 0.22–0.37). 12 Techniques that employ automatic quantification of tomographic abnormalities can be used to assess the progression of the extent of pulmonary impairment over time in COVID-19. A Brazilian study found pulmonary abnormalities in 80% of patients evaluated 90 days after hospital discharge, with ground-glass opacities and parenchymal bands as the predominant lesions.…”
mentioning
confidence: 99%